Die zivilrechtliche Haftung für autonome Drohnen unter Einbezug von Zulassungs- und Betriebsvorschriften - Hänsenberger, Silvio (sui generis, 2018)
The characteristics and abilities of autonomous drones pose major challenges for liability law. Nowadays only personal injury and damage to property on the ground are covered by strict liability (Art. 64 para. 1 Swiss Aviation Act). Injured parties are in danger of being left without legal protection in the event of mid-air collisions, as claims for damages cannot be asserted on the basis of erroneous decisions by an algorithm, either through liability for wilful or negligent wrongdoing (Art. 41 para. 1 Swiss Code of Obligations) or product liability. The same applies to purely pecuniary loss. The question of liability for wilful or negligent wrongdoing arises only if duties of care were violated when using autonomous drones. Such duties of care may ensue from permit and operating regulations. Currently autonomous flights without the possibility of direct control and beyond a pilot's field of vision are allowed only with special permits. As international efforts show, such barriers will come down in future. Appropriate licensing and operating regulations as described in this dissertation will therefore be required. At the same time it will be necessary to extend strict liability under aviation law for unmanned aircraft that are not steered by a pilot to damage in the event of mid-air collisions and to purely pecuniary damage. The specific legal formulations and their legislative implementation are proposed and discussed here for this purpose.